2018
DOI: 10.21315/mjms2018.25.5.11
|View full text |Cite
|
Sign up to set email alerts
|

The Incontinence Praying Ability and the Incontinence Quality of Life Questionnaires for Muslim Women: A Confirmatory Study of the Malay Language Versions

Abstract: BackgroundThe aim of the present study was to determine the validity and reliability of the Malay versions of the Incontinence Praying Ability (I-PA) and the Incontinence Quality of Life (I-QoL) questionnaires among childbearing-aged Muslim women.MethodsThis cross-sectional study included 338 childbearing-aged Muslim women (mean age: 31.1 years; SD = 5.57) who attended clinics at Hospital Universiti Sains Malaysia. Confirmatory factor analysis was conducted to determine the construct validity of the Malay vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…Besides the physical, social, and psychological burden of urinary incontinence, some patients may carry themselves an additional burden due to a misunderstanding of their consequences regarding ablution and Prayer. In general, 76.6% of members felt apprehensive and on edge that if they passed urine, they would end up unclean and be denied Prayer until they did the ritual cleansing once more, which is consistent with a previous study [27]. As a result, some people may think that they had to wash more often and repeat ablution whenever they feel some dribbling and experience this as a heavy burden.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Besides the physical, social, and psychological burden of urinary incontinence, some patients may carry themselves an additional burden due to a misunderstanding of their consequences regarding ablution and Prayer. In general, 76.6% of members felt apprehensive and on edge that if they passed urine, they would end up unclean and be denied Prayer until they did the ritual cleansing once more, which is consistent with a previous study [27]. As a result, some people may think that they had to wash more often and repeat ablution whenever they feel some dribbling and experience this as a heavy burden.…”
Section: Discussionsupporting
confidence: 82%
“…Our study showed that 83.1% and 66.9% of participants had repeated ablutions and repeated prayers. The previous study reported a similar burden among Muslim Moroccan and Turkish migrant women in the Netherlands [11] and Pakistani women [27].…”
Section: Discussionmentioning
confidence: 66%
“…The IQOL was evaluated in 14 languages across seven studies. 25,30,32,33,35,37,92 All languages showed moderate or high-level evidence for sufficient internal consistency, except for Portuguese 30,37 which had low-level sufficient evidence, due to being downgraded for imprecision. Structural validity for the IQOL was investigated in six languages (Persian, Spanish, French, Swedish, German, and Malay), all showing high sufficient evidence.…”
Section: Ui-specific Instrumentsmentioning
confidence: 99%
“…For Muslim women, urinary incontinence is a more serious problem, as they say, prayers five times a day, and during prayers, their body, clothes, and place of prayers must be clean. Saying prayers requires concentration and wholeheartedness, and urinary incontinence prevents women from achieving these states 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…Saying prayers requires concentration and wholeheartedness, and urinary incontinence prevents women from achieving these states. 10,11 According to epidemiological studies, more than 40% of women throughout the world suffer from urinary incontinence. 7 However, based on the definitions and diagnostic methods, different prevalence rates have been reported in different studies, ranging from 15% to 69%, depending on the study population and its characteristics.…”
mentioning
confidence: 99%